Aromatic and heterocyclic perfluoroalkyl sulfides. Methods of preparation - Boiko, Vladimir N. (Beilstein Journal of Organic Chemistry, 2010)
This review covers all of the common methods for the syntheses of aromatic and heterocyclic perfluoroalkyl sulfides, a class of compounds which is finding increasing application as starting materials for the preparation of agrochemicals, pharmaceutical products and, more generally, fine chemicals. A systematic approach is taken depending on the mode of incorporation of the SRF groups and also on the type of reagents used.
Keywords: halex-process; perfluoroalkylation; perfluoroalkyl sulfides; SRF-introduction

Substituent constants for correlation analysis in chemistry and biology - Hansch, C.; Leo, A. (Wiley, 1979)

Inventory of industrial fluoro-biochemicals - Becker, A. (Eyrolles, 1996)

(untitled) - Leroux, F.; Jeschke, P.; Schlosser, M. (Chem. Rev., 2005)

Fluorinated Bio-Active Compounds in the Agricultural and Medical Fields - Langlois, D. R.; Dillard, T.; Large, S.; Roques, N. (Brussels, 1999)
Sept 13–15, 1999; Paper No 24.

Fluorinated Bio-Active Compounds in the Agricultural and Medical Fields - Yagupolskii, L. M.; Maletina, I. I.; Petko, K. I.; Fedyuk, D. V. (Brussels, 1999)
September 13–15, 1999; Paper No 17.

(untitled) - Yagupolskii, L. M.; Maletina, I. I.; Petko, K. I.; Fedyuk, D. V.; Handrock, R.; Shavaran, S. S.; Klebanov, B. M.; Herzig, S. (J. Fluorine Chem., 2001)

JP Patent - SmithKline Beckman Corp (1987)
Chem. Abstr. 1988, 108, 131604w.

Canada Patent - Ayerst, McKenna and Harrison, Inc (1989)
Chem. Abstr. 1989, 111, 174666x.

USSR Patent - Boiko, V. N.; Shchupak, G. M.; Karabanov, Yu. V. et al. (1994)
Chem. Abstr. 1995, 123, 308709x.

USSR Patent - Dashevskaya, T. A.; Shalamay, A. S.; Shchupak, G. M.; Boiko, V. N., et at (1987)
Otkrytiya, Izobret., 1987, 14, 255.

USSR Patent - Gubnitskaya, E. S.; Boiko, V. N.; Kremlev, M. M. (1993)
Chem. Abstr. 1996, 124, 261367n.

(untitled) - Mizerski, A.; Gajadhur, A.; Pioro, S.; Ochal, Z. (Chem. Environ. Res., 2002)
Chem. Abstr. 2004, 140, 27628g.

Eur. Patent - Keil, S.; Wendler, W.; Glien, M.; Goerlitzer, J.; Chandross, K.; McGarry, D. G.; Merrill, J.; Bernardelli, P.; Ronan, B.; Terrier, C. (2005)
Chem. Abstr. 2005, 143, 387044r.

WO Patent - Gaudilliere, B.; Jacobelli, H. (2003)
Chem. Abstr. 2004, 140, 59649f.

U.S. Patent - Dalton, J. T.; Miller, D. D.; Yin, D.; He, Y. (2003)
Chem. Abstr. 2004, 140, 41912b.

U.S. Patent - Dalton, J. T.; Miller, D. D.; He, Y.; Yin, D. (2004)
Chem. Abstr. 2004, 140, 111132y.

U.S. Patent - Branstetter, B. J.; Breitenbucher, J. G.; Lebsack, A. D.; Liu, J.; Rech, J. C.; Xiao, W. (2009)
Chem. Abstr. 2009, 151, 56868t.

U.S. Patent - Kompella, A. K.; Adibhatla, K. S.; Bhujanga, R.; Rachakonda, S.; Venkaiah, C. N. (2008)
Chem. Abstr. 2009, 150, 35385x.

Aromatic and Heterocyclic Compounds with Fluorine-Containing Substituents - Yagupolskii, L. M. (Naukova Dumka, 1988)

(untitled) - Dolbier, W. R., Jr (Chem. Rev., 1996)

(untitled) - Brace, N. O. (J. Fluorine Chem., 1999)

(untitled) - Yoshida, M.; Kamigata, N.; Sawada, H.; Nakayama, M. (J. Fluorine Chem., 1990)

(untitled) - Farnham, W. B. (Chem. Rev., 1996)

(untitled) - Uno, H.; Suzukib, H. (Synlett, 1993)

(untitled) - Burton, D. J.; Yang, Z.-Y. (Tetrahedron, 1992)

(untitled) - Haas, A.; Niemann, U. (Adv. Inorg. Chem. Radiochem., 1976)

(untitled) - Langlois, B. R.; Billard, T. (Synthesis, 2003)

(untitled) - Prakash, G. K. S.; Mandal, M. (J. Fluorine Chem., 2001)

(untitled) - Adams, D. J.; Clark, J. H.; Heath, P. A.; Hansen, L. B.; Sanders, V. C.; Tavener, S. J. (J. Fluorine Chem., 2000)

(untitled) - Singh, R. P.; Shreeve, J. M. (Tetrahedron, 2000)

(untitled) - Furin, G. G. (Zh. Org. Khim., 1997)
Chem. Abstr. 1998, 129, 135686f. Russ. J. Org. Chem.1997, 33, 1209–1242.

(untitled) - Prakash, G. K. S.; Yudin, A. K. (Chem. Rev., 1997)

(untitled) - Umemoto, T. (Chem. Rev., 1996)

(untitled) - Huang, W.-Y. (J. Fluorine Chem., 1992)

(untitled) - Koshechko, V. G.; Kiprianova, L. A. (Theor. Exp. Chem., 1999)
in Russian; Chem. Abstr., 1999, 131, 304443y; Theor. Exp. Chem. 1999, 35, 18–36 (Eng. Ed.).

(untitled) - McClinton, M. A.; McClinton, D. A. (Tetrahedron, 1992)

Uspekhi Khimii Ftora - Barbor, A. K.; Belf, L. I.; Bekston, M. V. (Khimiya, 1970)
translation from Advances in Fluorine Chemistry; Stacey, M.; Tatlow, J. C.; Sharpe, A. G., Ed.; Butterworths Scientific Publication: London, 1963–1965; Vol. 3–4.

Patent D.R.P. - I. G. Farbenind (1936)
Blst. 1965, 6, III, 1009, 1033, 1034, 1038, 1067.

Patent US - Muller, F.; Scherer, O.; Schumacher, W. (1938)
Chem. Abstr. 1938, 32, 2958.

Fr. Patent - I.G. Farbenindustrie (1937)
Zbl. 1938, 1, 1876.

U.S. Patent - Gregory, W. A. (1956)
Chem. Abstr. 1957, 51, 4429c.

U.S. Patent - Gregory, W. G. (1957)
Chem. Abstr. 1957, 51, 15571c.

U.S. Patent - Buchanan, J. B.; Gregory, W. A. (1962)
Chem. Abstr. 1963, 58, 10127d.

(untitled) - Nodiff, E. A.; Lipsehutz, S.; Craig, P. N.; Gordon, M. (J. Org. Chem., 1960)

(untitled) - Yagupolskii, L. M.; Marenets, M. S. (Zh. Obshch. Khim., 1956)

(untitled) - Yagupolskii, L. M.; Kiprianov, A. I. (Zh. Obshch. Khim., 1952)
Chem. Abstr. 1953, 47, 4771a.

(untitled) - Yagupolskii, L. M.; Marenets, M. S. (Zh. Obshch. Khim., 1954)
Chem. Abstr. 1955, 49, 8172e; J. Gen. Chem. U.S.S.R. 1954, 24, 885–891.

(untitled) - Yagupolskii, L. M.; Gandelsman, L. Z.; Trushanina, L. I. (Ukr. Khim. Zh., 1965)
Chem. Abstr. 1966, 64, 14315g.

(untitled) - Yagupolskii, L. M.; Marenets, M. S. (Zh. Obshch. Khim., 1959)
Chem. Abstr. 1959, 53, 21765i.

(untitled) - Yagupolskii, L. M.; Gruz, B. E. (Zh. Obshch. Khim., 1961)
Chem. Abstr. 1961, 55, 24720i.

(untitled) - Gandelsman, L. Z.; Mostoslavskaya, E. I.; Yagupolskii, L. M. (Ukr. Khim. Zh., 1975)
Chem. Abstr. 1975, 82, 172578d.

(untitled) - Yagupolskii, L. M.; Orda, V. V. (Zh. Obshch. Khim., 1964)
Chem. Abstr. 1964, 61, 8217b.

(untitled) - Yagupolskii, L. M.; Boiko, V. N. (Zh. Obshch. Khim., 1969)
Chem. Abstr. 1969, 70, 96324c.

WO - Tohyama, Y.; Kanematsu, K.; PCT Int. Appl (2009)
Chem. Abstr. 2009, 150, 144137p.

(untitled) - Yagupolskii, L. M.; D′yachenko, E. B.; Troitskaya, V. I. (Ukr. Khim. Zh., 1961)
Chem. Abstr. 1961, 55, 21029a.

(untitled) - Ponticello, G. S.; Hartman, R. D.; Lumma, W. C.; Baldwin, J. J. (J. Org. Chem., 1979)

(untitled) - Knunyants, I. L.; Fokin, A. V. (Izv. Akad. Nauk SSSR, Ser. Khim., 1952)
Chem. Abstr. 1953, 47, 3221b.

(untitled) - England, D. C.; Melby, L. R.; Dietrich, M. A.; Lindsey, R. V., Jr (J. Am. Chem. Soc., 1960)

(untitled) - Langlois, B.; Desbois, M. (Actual. Chim., 1987)
Chem. Abstr. 1988, 108, 149998n.

(untitled) - Wakselman, C.; Kaziz, C. (J. Fluorine Chem., 1986)

(untitled) - Umemoto, T.; Ishihara, S. (J. Fluorine Chem., 1998)

(untitled) - Guo, Y.; Chen, Q.-Y. (J. Fluorine Chem., 2000)

(untitled) - Xing-ya, L.; He-qi, P.; Wei-min, F.; Xi-kui, J. (J. Fluorine Chem., 1986)

(untitled) - Li, X.-y.; Jiang, X.-k.; Pan, H.-q.; Hu, J.-s.; Fu, W.-m. (Pure Appl. Chem., 1987)

(untitled) - Suda, M.; Hino, C. (Tetrahedron Lett., 1981)

Eur. Patent - Siegrist, U.; Intermuehle, J.; Baumeister, P. (1986)
Chem. Abstr. 1986, 105, 60409.

Ger. Patent - Gassen, K. R.; Marhold, A. (1990)
Chem. Abstr. 1990, 113, 211569g.

(untitled) - Jouen, C.; Lasne, M. C.; Pommelet, J. C. (Tetrahedron Lett., 1996)

Belg. Patent - Richert, H. (1963)
Chem. Abstr. 1963, 59, 305.

(untitled) - Andreades, S.; Harris, J. F., Jr; Sheppard, W. A. (J. Org. Chem., 1964)

WO Patent - Lee, H.-S.; Geng, L.; Skotheim, T. (1996)
U.S. Patent 5,538,812, 1996; Chem. Abstr. 1996, 125, 147119d.

(untitled) - Scribner, R. M. (J. Org. Chem., 1966)

U.S. Patent - Scribner, R. M. (1968)
Chem. Abstr. 1968, 69, 76945g.

(untitled) - Croft, T. S. (Phosphorus Sulfur Relat. Elem., 1976)

(untitled) - Croft, T. S. (Phosphorus Sulfur Relat. Elem., 1976)

(untitled) - Emeléus, H. J.; Nabi, S. N. (J. Chem. Soc., 1960)

(untitled) - Haas, A.; Hellwig, V. (J. Fluorine Chem., 1975)

(untitled) - Sheppard, W. A. (J. Org. Chem., 1964)

(untitled) - Popov, V. I.; Kondranenko, N. V.; Haas, A. (Ukr. Khim. Zh., 1983)
Chem. Abstr. 1983, 99, 194535r.

(untitled) - Haas, A.; Niemann, U. (Chem. Ber., 1977)

(untitled) - Mirek, J.; Haas, A. (J. Fluorine Chem., 1981)

(untitled) - Gerstenberger, M. R. C.; Haas, A.; Liebig, F. (J. Fluorine Chem., 1982)

(untitled) - Croft, T. S.; McBrady, J. J. (J. Heterocycl. Chem., 1975)
Chem. Abstr. 1976, 84, 43948s.

(untitled) - Gerstenberger, M. R. C.; Haas, A. (J. Fluorine Chem., 1983)

(untitled) - Haas, A.; Hellwig, V. (Chem. Ber., 1976)

(untitled) - Haas, A.; Niemann, U. (J. Fluorine Chem., 1978)

(untitled) - Dorn, S.; Eggenberg, P.; Gerstenberger, M. R. C.; Haas, A.; Niemann, U.; Zobrist, P. (Helv. Chim. Acta, 1979)

Uspekhi Khimii Ftora - Clark, N. K. (Khimiya, 1970)
translation from Advances in Fluorine Chemistry; Stacey, M.; Tatlow, J. C.; Sharpe, A. G., Ed.; Butterworths Scientific Publication: London, 1963–1965; Vol. 3–4.

(untitled) - Man, E. H.; Coffman, D. D.; Muetterties, E. L. (J. Am. Chem. Soc., 1959)

(untitled) - Emeléus, H. J.; MacDuffie, D. E. (J. Chem. Soc., 1961)

(untitled) - Orda, V. V.; Yagupolskii, L. M.; Bystrov, V. F.; Stepanyants, A. U. (Zh. Obshch. Khim., 1965)
Chem. Abstr. 1965, 63, 17861c.

(untitled) - Harris, J. F., Jr (J. Org. Chem., 1967)

(untitled) - Yagupolskii, L. M.; Kondratenko, N. V.; Sambur, V. P. (Synthesis, 1975)

(untitled) - Kondratenko, N. V.; Kolomeytsev, A. A.; Popov, V. I.; Yagupolskii, L. M. (Synthesis, 1985)

(untitled) - Oksengendler, I. G.; Kondratenko, N. V.; Luk′yanets, E. A.; Yagupolskii, L. M. (Zh. Org. Khim., 1978)
Chem. Abstr. 1978, 89, 112289v.

(untitled) - Kolomeitsev, A. A.; Kondratenko, N. V.; Popov, V. I.; Yagupolskii, L. M. (Zh. Org. Khim., 1983)
Chem. Abstr. 1984, 100, 209281v.

(untitled) - Pazenok, S. V.; Kondratenko, N. V.; Popov, V. I.; Troitskaya, V. I.; Il′chenko, A. Ya.; Al′perovich, M. A.; Yagupolskii, L. M. (Khim. Geterotsikl. Soedin., 1983)
Chem. Abstr. 1984, 100, 53186e.

(untitled) - Boiko, V. N.; Shchupak, G. M.; Yagupolskii, L. M. (Zh. Org. Khim., 1980)
Chem. Abstr. 1980, 93, 167794u.

USSR Patent - Yagupolskii, L. M.; Sambur, V. P.; Kondratenko, N. V. (1975)
Otkrytiya, Izobret., Prom. Obraztsy 1975, 9, 60; Chem. Abstr. 1975, 83, 42811j.

(untitled) - Clark, J. H.; Jones, C. W.; Kybett, A. P.; McClinton, M. A.; Miller, J. M.; Bishop, D.; Blade, R. J. (J. Fluorine Chem., 1990)

(untitled) - Remy, D. C.; Rittle, K. E.; Hunt, C. A.; Freedman, M. B. (J. Org. Chem., 1976)

U.S. Patent - Remy, D. C.; Freedman, M. B. (1977)
Chem. Abstr. 1977, 87, 52939d.

(untitled) - Munavalli, S.; Rossman, D. I.; Rohrbaugh, D. K.; Ferguson, C. P.; Hsu, F.-L. (Heteroat. Chem., 1992)

(untitled) - Munavalli, S.; Hassner, A.; Rossman, D. I.; Singh, S.; Rohrbaugh, D. K.; Ferguson, C. P. (J. Fluorine Chem., 1995)

(untitled) - Kitazume, T.; Ishikawa, N. (Bull. Chem. Soc. Jpn., 1975)

(untitled) - Chen, Q.-Y.; Duan, J.-X. (Chem. Commun., 1993)

(untitled) - Kolomeitsev, A.; Medebielle, M.; Kirsch, P.; Lork, E.; Roschenthaler, G.-V. (J. Chem. Soc., Perkin Trans. 1, 2000)

(untitled) - Haas, A.; Klug, W. (Chem. Ber., 1968)

(untitled) - Dmowski, W.; Haas, A. (Chimia, 1985)

(untitled) - Dmowski, W.; Haas, A. (J. Chem. Soc., Perkin Trans. 1, 1987)

(untitled) - Dmowski, W.; Haas, A. (J. Chem. Soc., Perkin Trans. 1, 1988)

(untitled) - Petrova, T. D.; Platonov, V. E.; Shchegoleva, L. N.; Maksimov, A. M.; Haas, A.; Schelvis, M.; Lieb, M. (J. Fluorine Chem., 1996)

(untitled) - Clark, J. H.; Tavener, S. J. (J. Fluorine Chem., 1997)

(untitled) - Tavener, S. J.; Adams, D. J.; Clark, J. H. (J. Fluorine Chem., 1999)

(untitled) - Tyrra, W.; Naumann, D.; Hoge, B.; Yagupolskii, Yu. L. (J. Fluorine Chem., 2003)

(untitled) - Jellinek, F. (Proc. Chem. Soc., London, 1959)

(untitled) - Jellinek, F.; Lagowski, J. J. (J. Chem. Soc., 1960)

(untitled) - Adams, D. J.; Clark, J. H. (J. Org. Chem., 2000)

(untitled) - Haas, A.; Heuduk, H.; Monsé, C.; Yagupolskii, L. M. (J. Fluorine Chem., 1999)

(untitled) - Kondratenko, N. V.; Sambur, V. P. (Ukr. Khim. Zh., 1975)
Chem. Abstr. 1975, 83, 58321k.

(untitled) - Adams, D. J.; Goddard, A.; Clark, J. H.; Macquarrie, D. J. (Chem. Commun., 2000)

(untitled) - Banus, J.; Emeléus, H. J.; Haszeldine, R. N. (J. Chem. Soc., 1951)

(untitled) - Pierce, O. R.; McBee, E. T.; Judd, G. F. (J. Am. Chem. Soc., 1954)

(untitled) - McBee, E. T.; Roberts, C. W.; Curtis, S. G. (J. Am. Chem. Soc., 1955)

(untitled) - Chambers, R. D.; Musgrave, W. K. R.; Savory, J. (J. Chem. Soc., 1962)

(untitled) - Johncock, P. (J. Organomet. Chem., 1969)

(untitled) - Lagowskii, J. J. (Q. Rev., Chem. Soc., 1959)

Obschaya Khimiya - Pouling, L. (Mir, 1974)
translation from Pouling, L. General Chemistry, W. H. Freeman and Co; San-Francisco, 1970.

(untitled) - Haley, B.; Haszeldine, R. N.; Hewitson, B.; Tipping, A. E. (J. Chem. Soc., Perkin Trans. 1, 1976)

(untitled) - Haszeldine, R. N.; Higginbottom, B.; Rigby, R. B.; Tipping, A. E. (J. Chem. Soc., Perkin Trans. 1, 1972)

(untitled) - Haszeldine, R. N.; Rigby, R. B.; Tipping, A. E. (J. Chem. Soc., Perkin Trans. 1, 1972)

(untitled) - Huyser, E. S.; Bedard, E. (J. Org. Chem., 1964)

(untitled) - Kimoto, H.; Fujii, S.; Cohen, L. A. (J. Org. Chem., 1982)

(untitled) - Kornblum, N.; Davies, T. M.; Earl, G. W.; Holy, N. L.; Kerber, R. C.; Musser, M. T.; Snow, D. H. (J. Am. Chem. Soc., 1967)

(untitled) - Kornblum, N.; Davies, T. M.; Earl, G. W.; Greene, G. S.; Holy, N. L.; Kerber, R. C.; Manthey, J. W.; Musser, M. T.; Snow, D. H. (J. Am. Chem. Soc., 1967)

(untitled) - Kornblum, N.; Boyd, S. D.; Ono, N. (J. Am. Chem. Soc., 1974)

(untitled) - Kornblum, N. (Angew. Chem., 1975)

(untitled) - Bunnett, J. F.; Kim, J. K. (J. Am. Chem. Soc., 1970)

(untitled) - Bunnett, J. F.; Kim, J. K. (J. Am. Chem. Soc., 1970)

(untitled) - Bunnett, J. F.; Creary, X. (J. Org. Chem., 1974)

(untitled) - Bunnett, J. F.; Creary, X. (J. Org. Chem., 1974)

(untitled) - Bunnett, J. F.; Creary, X. (J. Org. Chem., 1975)

(untitled) - Boiko, V. N.; Shchupak, G. M.; Yagupolskii, L. M. (Zh. Org. Khim., 1977)
Chem. Abstr. 1977, 87, 134226h.

(untitled) - Popov, V. I.; Boiko, V. N.; Kondratenko, N. V.; Sambur, V. P.; Yagupolskii, L. M. (Zh. Org. Khim., 1977)
Chem. Abstr. 1978, 88, 104823d.

(untitled) - Boiko, V. N.; Dashevskaya, T. A.; Shchupak, G. M.; Yagupolskii, L. M. (Zh. Org. Khim., 1979)
Chem. Abstr. 1979, 91, 20439g.

USSR Patent - Boiko, V. N.; Shchupak, G. M.; Popov, V. I.; Orlova, R. K.; Yagupol'skii, L. M.
Chem. Abstr. 1980, 92, 22503t.

(untitled) - Voloshchuk, V. G.; Boiko, V. N.; Yagupolskii, L. M. (Zh. Org. Khim., 1977)
Chem. Abstr. 1978, 88, 6483y.

(untitled) - Kondratenko, N. V.; Popov, V. I.; Kolomeitsev, A. A.; Sadekov, I. D.; Minkin, V. I.; Yagupolskii, L. M. (Zh. Org. Khim., 1979)
Chem. Abstr. 1979, 91, 174948j.

USSR Patent - Boiko, V. N.; Shchupak, G. M.; Kirii, N. V.; Kharchuk, A. N. (2004)

(untitled) - Kondratenko, N. V.; Yurchenko, L. G.; Matyushecheva, G. I. (Ukr. Khim. Zh., 1981)
Chem. Abstr. 1981, 95, 186790x.

(untitled) - Kondratenko, N. V.; Kolomeitsev, A. A.; Popov, V. I.; Il′chenko, A. Ya. (Zh. Obshch. Khim., 1983)
Chem. Abstr. 1984, 100, 50987f.

(untitled) - Kondratenko, N. V.; Popov, V. I.; Kolomeitsev, A. A.; Saenko, E. P.; Prezhdo, V. V.; Lutskii, A. E.; Yagupolskii, L. M. (Zh. Org. Khim., 1980)
Chem. Abstr. 1980, 93, 185545t.

NO Patent - Fugitt, R. B.; Luckenbaugh, R. W. (Analogifremgangsmaate for fremstilling av terapeutisk virksomme 3-(p-alkylsulfonylfenyl)-oxa-zolidinon-derivater, 1987)

(untitled) - Fedyuk, D. V.; Maletina, I. I.; Yagupolskii, L. M. (Ukr. Khim. Zh., 1997)
Chem. Abstr. 1999, 130, 182407w.

(untitled) - Fisher, I. P.; Homer, J. B.; Lossing, F. P. (J. Am. Chem. Soc., 1965)

(untitled) - Rempel, G. D.; Borisov, Yu. A.; Rayevskii, N. I.; Igumnov, S. M.; Rozhkov, I. N. (Izv. Akad. Nauk SSSR, Ser. Khim., 1990)
Chem. Abstr. 1990, 113, 96744w.

(untitled) - Gandel′sman, L. Z.; Boiko, V. N. (Ukr. Khim. Zh., 1977)
Chem. Abstr. 1978, 88, 89253x.

UA Patent - Boiko, V. N.; Kirii, N. V.; Shchupak, G. M. (1994)
Promyslova Vlasnist 1994, 8-I, 3.142; Chem. Abstr. 1996, 124, 116859v.

RU Patent - Boiko, V. N.; Kirii, N. V.; Shchupak, G. M. (1995)
Chem. Abstr. 1996, 124, 116859v.

(untitled) - Uneyama, K.; Kitagawa, K. (Tetrahedron Lett., 1991)

(untitled) - Uneyama, K.; Kanai, M. (Tetrahedron Lett., 1991)

(untitled) - Boiko, V. N.; Shchupak, G. M.; Yagupolskii, L. M. (Zh. Org. Khim., 1985)
Chem. Abstr. 1986, 104, 206815u.

(untitled) - Boiko, V. N.; Shchupak, G. M.; Ignat’ev, N. V.; Yagupolskii, L. M. (Zh. Org. Khim., 1979)
Chem. Abstr. 1979, 91, 157378f.

(untitled) - Havinga, E.; Kronenberg, M. E. (Pure Appl.Chem., 1968)

(untitled) - Yavorskii, A. E.; Stetsenko, A. V.; Gogoman, I. V.; Boiko, V. N. (Khim. Geterotsikl. Soedin., 1988)
Chem. Abstr. 1989, 110, 114751r.

(untitled) - Laser, E. S.; Matteo, M. R.; Possanza, G. J. (J. Med. Chem., 1987)

(untitled) - Popov, V. I.; Boiko, V. N.; Yagupolskii, L. M. (J. Fluorine Chem., 1982)

DE Patent - Huebl, D.; Puttner, R.; Richter, E.; Pieroh, E.-A. (2-Imino-1,3-dithietanes, their preparation and their use as pesticides, 1988)
Chem. Abstr. 1988, 109, 170410v.

(untitled) - Chen, Q.-Y.; Chen, M.-J. (J. Fluorine Chem., 1991)

(untitled) - Rico, I.; Cantacuzene, D.; Wakselman, C. (J. Org. Chem., 1983)

(untitled) - Rico, I.; Wakselman, C. (J. Fluorine Chem., 1982)

Uspekhy Khim. Ftora - Patric, S. (Khimia, 1964)
Translation from Advances in Fluorine Chemistry, Butterworths Science Publ.: London, U.K., 1960–1961; Vol. I–II.

(untitled) - Andrieux, C. P.; Gelis, L.; Medebielle, M.; Pinson, J.; Saveant, J. M. (J. Am. Chem. Soc., 1990)

(untitled) - Ignat′ev, N. V.; Boiko, V. N.; Yagupolskii, L. M. (Zh. Org. Khim., 1985)
Chem. Abstr. 1985, 103, 141549t.

USSR Patent - Ignat′ev, N. V.; Boiko, V. N.; Yagupolskii, L. M. (1985)
Otkrytiya, Izobret., Prom. Obraztsy 1985, 26, 108.

(untitled) - Wakselman, C.; Tordeux, M. (J. Chem. Soc., Chem. Commun., 1984)

FR Patent - Tordeux, M.; Wakselman, C. (Procede de preparation de perhalogenoalkylthioethers, 1985)
Chem.Abstr. 1985, 102, 45480x.

(untitled) - Wakselman, C.; Tordeux, M. (J. Org. Chem., 1985)

(untitled) - Boiko, V. N.; Shchupak, G. M.; Kirij, N. V. (Ukr. Khim. Zh., 2001)

(untitled) - Bunnett, J. F.; Scamehorn, R. G.; Traber, R. P. (J. Org. Chem., 1976)

Abstracts of Papers - Koshechko, V. G.; Kiprianova, L. A.; Fileleeva, L. I.; Boiko, V. N. (6th Vsesoyuznaya konferentsiya po organicheskoi khimii, 10.10.1988-14.10.1988)

(untitled) - Ignat′ev, N. V.; Datsenko, S. D.; Yagupolskii, L. M. (Zh. Org. Khim., 1991)
Chem. Abstr. 1992, 116, 58861m.

(untitled) - Datsenko, S. D.; Ignat′ev, N. V.; Yagupolskii, L. M. (Elektrokhimiya, 1991)
Chem. Abstr. 1992, 116, 115486u.

(untitled) - Medebielle, M.; Pinson, J.; Saveant, J. M. (J. Am. Chem. Soc., 1991)

(untitled) - Kitazume, T.; Ikeya, T. (J. Org. Chem., 1988)

(untitled) - Koshechko, V. G.; Kiprianova, L. A.; Fileleeva, L. I. (Tetrahedron Lett., 1992)

(untitled) - Petrov, V. A. (Tetrahedron Lett., 2001)

(untitled) - Feiring, A. E. (J. Fluorine Chem., 1984)

(untitled) - Boiko, V. N.; Shchupak, G. M. (J. Fluorine Chem., 1994)

(untitled) - Wakselman, C.; Tordeux, M. (Bull. Soc. Chim. Fr., 1986)

(untitled) - Tordeux, M.; Langlois, B.; Wakselman, C. (J. Org. Chem., 1989)

(untitled) - Tordeux, M.; Langlois, B.; Wakselman, C. (J. Chem. Soc., Perkin Trans. 1, 1990)

EU Patent - Clavel, J. L.; Langlois, B.; Nantermet, R.; Tordeux, M.; Wakselman, C. (Process for the preparation of perhalogen alkyl thio ethers, 1990)
Chem.Abstr. 1991, 114, 5483s.

(untitled) - Folest, J.-C.; Nédélec, J.-Y.; Périchon, J. (Synth. Commun., 1988)

(untitled) - Andrieux, C. P.; Gelis, L.; Saveant, J. M. (J. Am. Chem. Soc., 1990)

(untitled) - Wakselman, C.; Tordeux, M.; Clavel, J.-L.; Langlois, B. (J. Chem. Soc., Chem. Commun., 1991)

(untitled) - Clavel, J.-L.; Langlois, B.; Nantermet, R.; Tordeux, M.; Wakselman, C. (J. Chem. Soc., Perkin Trans. 1, 1992)

(untitled) - Magnier, E.; Vit, E.; Wakselman, C. (Synlett, 2001)

(untitled) - Koshechko, V. G.; Kiprianova, L. A.; Fileleeva, L. I.; Rozhkova, Z. Z. (Teor. Eksp. Khim., 1993)
Chem. Abstr. 1994, 121, 120151p.

(untitled) - Koshechko, V. G.; Kiprianova, L. A.; Fileleeva, L. I.; Rozhkova, Z. Z. (J. Fluorine Chem., 1995)

(untitled) - Joglekar, B.; Miyake, T.; Kawase, R.; Shibata, K.; Muramatsu, H.; Matsui, M. (J. Fluorine Chem., 1995)

(untitled) - Koshechko, V. G.; Kiprianova, L. A.; Fileleeva, L. I.; Tsanov, K. G. (J. Fluorine Chem., 1999)

(untitled) - Koshechko, V. G.; Kiprianova, L. A.; Fileleeva, L. I.; Kalinina, L. I. (J. Fluorine Chem., 2007)

(untitled) - Feiring, A. E.; Wonchoba, E. R.; Arthur, S. D. (J. Polym. Sci. Polym. Chem. Ed., 1990)

(untitled) - Su, D.; Chen, Q.; Zhu, R. (Youji Huaxue, 1986)
Chem. Abstr. 1986, 105, 225915p.

JP Patent - Nishi, M.; Narita, K. (Production of aminophenyl alkyl sulfide, 1998)
Chem.Abstr. 1999, 130, 3685r.

(untitled) - Ward, W.; Sicree, S.; Chen, B.; Tamborski, C. (J. Fluorine Chem., 1995)

(untitled) - Wakselman, C. (J. Fluorine Chem., 1992)

(untitled) - Rozhkov, I. N.; Igumnov, S. M.; Becker, G. Ya.; Pletn′ev, S. I. (Izv. Akad. Nauk SSSR, Ser. Khim., 1989)
Chem. Abstr. 1990, 112, 76153d.

(untitled) - Kobayashi, Y.; Kumadaki, I.; Ohsawa, A.; Murakami, S.-I.; Nakano, T. (Chem. Pharm. Bull., 1978)

(untitled) - Haszeldine, R. N.; Rigby, R. B.; Tipping, A. E. (J. Chem. Soc., Perkin Trans. 1, 1972)

JP Patent - Sagami Chemical Research Center (1981)
Chem. Abstr. 1982, 96, 85048b.

(untitled) - Umemoto, T.; Miyano, O. (Tetrahedron Lett., 1982)

(untitled) - Umemoto, T.; Ando, A. (Bull. Chem. Soc. Jpn., 1986)

(untitled) - Sekiya, A.; Umemoto, T. (Chem. Lett., 1982)

(untitled) - Barton, D. H. R.; Lacher, B.; Zard, S. Z. (Tetrahedron, 1986)

(untitled) - Barton, D. H. R.; Lacher, B.; Zard, S. Z. (Tetrahedron, 1987)

(untitled) - Billard, T.; Roques, N.; Langlois, B. R. (J. Org. Chem., 1999)

(untitled) - Billard, T.; Roques, N.; Langlois, B. R. (Tetrahedron Lett., 2000)

(untitled) - Tanabe, Y.; Matsuo, N.; Ohno, N. (J. Org. Chem., 1988)

(untitled) - Sipyagin, A. M.; Pomytkin, I. A.; Pal′tsun, S. V.; Aleinikov, N. N.; Kartsev, V. G. (Dokl. Akad. Nauk SSSR, 1990)
Chem. Abstr. 1990, 113, 152212k.

(untitled) - Sipyagin, A. M.; Pomytkin, I. A.; Pal′tsun, S. V.; Aleinikov, N. N. (Khim. Geterotsikl. Soedin., 1994)
Chem. Abstr. 1995, 122, 31274j.

(untitled) - Sipyagin, A. M.; Enshov, V. S.; Boiko, G. N.; Lebedev, A. T.; Karakhanova, N. K. (Khim. Geterotsikl. Soedin., 2003)
In Russian.

(untitled) - Sipyagin, A. M.; Efremov, I. V.; Pomytkin, I. A.; Kashtanov, S. A.; Aleinikov, N. N. (Khim. Geterotsikl. Soedin., 1994)
Chem. Abstr. 1995, 122, 239503r.

(untitled) - Enshov, V. S.; Kashtanov, S. A.; Efremov, I. V.; Pomytkin, I. A.; Sipyagin, A. M. (Khim. Geterotsikl. Soedin., 1995)
Chem. Abstr. 1996, 125, 33451a.

(untitled) - Sipyagin, A. M.; Enshov, V. S.; Lebedev, A. T.; Karakhanova, N. K. (Khim. Geterotsikl. Soedin., 2003)
In Russian.

(untitled) - Sipyagin, A. M.; Enshov, V. S.; Kashtanov, S. A.; Treshcher, D. S. (Khim. Geterotsikl. Soedin., 2002)
In Russian.

(untitled) - Clavel, J.-L.; Langlois, B.; Laurent, E.; Roidot, N. (Phosphorus, Sulfur Silicon Relat. Elem., 1991)

EP Patent - Clavel, J.-L.; Laurent, E.; Langlois, B.; Roidot, N. (Reagent and process for the perfluoroalkylation of nucleophilic substrates by sodium perfluoroalkanesulfinates in an oxidising medium, 1991)
Chem. Abstr. 1992, 116, 127821n.

(untitled) - Kirij, N. V.; Pasenok, S. V.; Yagupolskii, Yu. L.; Tyrra, W.; Naumann, D. (J. Fluorine Chem., 2000)

(untitled) - Kondratenko, N. V.; Popov, V. I.; Yurchenko, L. G.; Kolomeitsev, A. A.; Yagupolskii, L. M. (Zh. Org. Khim., 1978)
Chem. Abstr. 1979, 90, 54603a.

(untitled) - Zeifman, Yu. V.; Lantseva, L. T.; Knunyants, I. L. (Izv. Akad. Nauk SSSR, Ser. Khim., 1978)
Chem. Abstr. 1979, 91, 56281p.

(untitled) - Suzuki, H.; Satake, H.; Uno, H.; Shimizu, H. (Bull. Chem. Soc. Jpn., 1987)

JP Patent - Suzuki, H.; Uno, H.; Shimizu, H.; Nemoto, F. (Production of perfluoroalkylaryl sulfide, 1988)
Chem. Abstr. 1988, 109, 73127a.

(untitled) - Zeifman, Yu. V.; Lantseva, L. T.; Knunyants, I. L. (Izv. Akad. Nauk SSSR, Ser. Khim., 1978)
Chem. Abstr. 1978, 89, 146381j.

(untitled) - Zeifman, Yu. V.; Lantseva, L. T. (Izv. Akad. Nauk SSSR, Ser. Khim., 1980)
Chem. Abstr. 1980, 93, 113882c.

(untitled) - Nguyen, T.; Rubinstein, M.; Wakselman, C. (J. Org. Chem., 1981)

(untitled) - Tordeux, M.; Francese, C.; Wakselman, C. (J. Fluorine Chem., 1989)

(untitled) - Pooput, C.; Médebielle, M.; Dolbier, W. R., Jr. (Org. Lett., 2004)

(untitled) - Pooput, C.; Dolbier, W. R., Jr.; Médebielle, M. (J. Org. Chem., 2006)

(untitled) - Billard, T.; Langlois, B. R. (Tetrahedron Lett., 1996)

(untitled) - Quiclet-Sire, B.; Saicic, R. N.; Zard, S. Z. (Tetrahedron Lett., 1996)

(untitled) - Russell, J.; Roques, N. (Tetrahedron, 1998)

(untitled) - Large, S.; Roques, N.; Langlois, B. R. (J. Org. Chem., 2000)

(untitled) - Roques, N. (J. Fluorine Chem., 2001)

(untitled) - Blond, G.; Billard, T.; Langlois, B. R. (Tetrahedron Lett., 2001)

(untitled) - Inschauspe, D.; Sortais, J.-B.; Billard, T.; Langlois, B. R. (Synlett, 2003)

(untitled) - Prakash, G. K. S.; Hu, J.; Olah, G. A. (Org. Lett., 2003)

EP Patent - Popkova, V. Y.; Marhold, A. (Process for the preparation of perfluoalkylaryl sulfides and perfluoroalkylaryl sulfides per se, 1999)
Chem. Abstr. 2000, 132, 3248s.

Chemistry of organic fluorine compounds II. A Critical Review (ACS Monograph 187) - Hudlicky, M.; Pavlath, A. E. (American Chemical Society, 1995)

Aliphaticheskie fluorine-containing compounds - Lovelace, A. M.; Rausch, D. A.; Postelnek, M. (Inostrannaya Literatura, 1961)
Translation from Aliphatic Fluorine compounds ACS Monograph Series: N.Y., London.

(untitled) - Emeléus, H. J.; Haszeldine, R. N. (J. Chem. Soc., 1949)

(untitled) - Haszeldine, R. N. (J. Chem. Soc., 1954)

(untitled) - McBee, E. T.; Battershell, R. D.; Braendlin, H. P. (J. Org. Chem., 1963)

(untitled) - Emeléus, H. J.; Haszeldine, R. N. (J. Chem. Soc., 1949)

(untitled) - Burton, D. J.; Hahnfeld, J. L. (J. Org. Chem., 1977)

(untitled) - Schlosser, M.; Heinz, G.; Chau, L. V. (Chem. Ber., 1971)

(untitled) - Schlosser, M.; Heinz, G. (Chem. Ber., 1971)

(untitled) - Chang, Y.; Cai, C. (J. Fluorine Chem., 2005)

(untitled) - Folléas, B.; Marek, I.; Normant, J.-F.; Saint-Jalmes, L. (Tetrahedron, 2000)

(untitled) - Shono, T.; Ishifune, M.; Okada, T.; Kashimura, S. (J. Org. Chem., 1991)

WO Appl. - Roques, N.; Russell, J. (1997)
Chem. Abstr. 1997, 127, 50384q.

(untitled) - Folléas, B.; Marek, I.; Normant, J.-F.; Saint-Jalmes, L. (Tetrahedron Lett., 1998)

(untitled) - Billard, T.; Langlois, B. R.; Blond, G. (Eur. J. Org. Chem., 2001)

Synthetic Fluorine Chemistry - Olah, G. A.; Chambers, R. D.; Prakash, G. K. S. (Wiley-Interscience, 1992)

(untitled) - Ruppert, I.; Schlich, K.; Volbach, W. (Tetrahedron Lett., 1984)

(untitled) - Kolomeitsev, A. A.; Movchun, V. N.; Kondratenko, N. V.; Yagupolskii, Yu. L. (Synthesis, 1990)

(untitled) - Patel, N. R.; Kirchmeier, R. L. (Inorg Chem., 1992)

(untitled) - Singh, R. P.; Cao, G.; Kirchmeier, R. L.; Shreeve, J. M. (J. Org. Chem., 1999)

(untitled) - Movchun, V. N.; Kolomeitsev, A. A.; Yagupolskii, Yu. L. (J. Fluorine Chem., 1995)

(untitled) - Billard, T.; Large, S.; Langlois, B. R. (Tetrahedron Lett., 1997)

(untitled) - Shein, S. M.; Krasnosel′skaya, M. I.; Boiko, V. N. (Zh. Obshch. Khim., 1966)
Chem. Abstr. 1967, 66, 94446n.

(untitled) - Steensma, R. W.; Galabi, S.; Tagat, J. R.; McCombie, S. W. (Tetrahedron Lett., 2001)

(untitled) - Barrera, M. D.; Cheburkov, Y.; Lamanna, W. M. (J. Fluorine Chem., 2002)

(untitled) - Yagupolskii, L. M.; Maletina, I. I.; Kondratenko, N. V.; Orda, V. V. (Synthesis., 1978)

(untitled) - Yagupolskii, L. M.; Mironova, A. A.; Maletina, I. I. (Zh. Org. Khim., 1980)
Chem. Abstr. 1980, 93, 26005a.

(untitled) - Umemoto, T.; Kuriu, Y. (Chem. Lett., 1982)

(untitled) - Eisenberger, P.; Gischig, S.; Togni, A. (Chem.–Eur. J., 2006)

(untitled) - Kieltsch, I.; Eisenberger, P.; Togni, A. (Angew. Chem., Int. Ed., 2007)

(untitled) - Yagupolskii, L. M.; Kondratenko, N. V.; Timofeeva, G. N. (Zh. Org. Khim., 1984)
Chem. Abstr. 1984, 100, 191494e.

(untitled) - Yang, J.-J.; Kirchmeier, R. L.; Shreeve, J. M. (J. Org. Chem., 1998)

(untitled) - Magnier, E.; Blazejewski, J.-C.; Tordeux, M.; Wakselman, C. (Angew. Chem., 2006)

(untitled) - Umemoto, T.; Ishihara, S. (J. Am. Chem. Soc., 1993)

(untitled) - Umemoto, N.; Ishihara, S. (Tetrahedron Lett., 1990)

(untitled) - Manteau, B.; Pazenok, S.; Vors, J. P.; Leroux, F. R. (J. Fluorine Chem., 2010)